The Low Representativeness of Unions in Latin America: A Wrong Interpretation - Canessa Montejo, Miguel Francisco (2016)
The level of membership of trade Unions in Latin America is low. This affects the level of representation of workers by the unions. However, this statement would leave aside the fact that the national legislation formally prevents a substantive number of workers to establish a union in the enterprise or in the industry. The present investigate clarifies this issue based on an analysis or the normative framework and based on official statistical data.